Original Research Retinoblastoma And Study Of Its Poor Prognostic Factors (Indian Journal of Applied-Basic Medical Sciences, 2021)
Aim: -To study Retinoblastoma (RB) and its prognostic factors for its poor outcome.  Purpose: The aim is to carry out prospective study in a group of diagnosed cases of retinoblastoma (RB) along  with variable prognostic factors. There are many socio economic and demographic aspects which impose serious  effect on prognosis of retinoblastoma. Outcome includes poor prognostic factors related to RB. Design: Prospective study Method: Here, we have a case series of six patients diagnosed with RB from January 2020 to July 2020 and discuss their clinical features, treatment, outcome and its prognostic factors. Detailed examination will be carried out and assessment will be done. Result: 6 patients were studied for 6 months and prognostics factors were evaluated. 66% patients had delayed  presentation, 33% belonged to lower socioeconomic class,16% were having associated family history. Conclusion: Delayed presentation is related to RB which is a risk factor for poor outcome. Poor literacy, low socioeconomic condition, treatment abandonment, and high clinical grading is found poor prognostic for RB outcome.
Keywords: Retinoblastoma; prognosis; chemotherapy; presentation